On the limit distribution of the correlogram of a stationary Gaussian process with weak decrease in correlation - Leonenko, N. N.; Portnova, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
An example of the non-Gaussian limit distribution of the statistical estimate of the correlation function of a stationary Gaussian process with unbounded spectral density (or with a nonintegrable correlation function) is given.